2019
DOI: 10.1038/s41419-019-1699-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FOXP4-AS1 is activated by PAX5 and promotes the growth of prostate cancer by sequestering miR-3184-5p to upregulate FOXP4

Abstract: Prostate cancer (PCa) is one of the major men malignancies worldwide. Long noncoding RNAs (lncRNAs) have been reported as essential regulators in human cancers, including PCa. In the present study, lncRNA forkhead box P4 antisense RNA 1 (FOXP4-AS1) was found to be highly expressed in TCGA PCa samples. Upregulation of FOXP4-AS1 was further validated in 64 PCa tissues and predicted poor prognosis in patients with PCa. Functionally, high FOXP4-AS1 level was associated with increased cell proliferation and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 32 publications
6
96
0
Order By: Relevance
“…Yang et al established that FOXP4-AS1 is significantly up-regulated in osteosarcoma tumor tissues, besides its high expression can significantly increase the danger of death and recurrence in patients with In vivo and in vitro functional experiments suggest that FOXP4-AS1 plays an oncogene role in PCa. 10 In this study, we have reported that patients with higher manifestation of FOXP4-AS1 in PDAC tumor tissues had significantly shorter OS times than patients with low FOXP4-AS1. Our results are consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Yang et al established that FOXP4-AS1 is significantly up-regulated in osteosarcoma tumor tissues, besides its high expression can significantly increase the danger of death and recurrence in patients with In vivo and in vitro functional experiments suggest that FOXP4-AS1 plays an oncogene role in PCa. 10 In this study, we have reported that patients with higher manifestation of FOXP4-AS1 in PDAC tumor tissues had significantly shorter OS times than patients with low FOXP4-AS1. Our results are consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 60%
“…Survival analysis found that patients with high expression of FOXP4‐AS1 had a poor outcome. In vivo and in vitro functional experiments suggest that FOXP4‐AS1 plays an oncogene role in PCa . In this study, we have reported that patients with higher manifestation of FOXP4‐AS1 in PDAC tumor tissues had significantly shorter OS times than patients with low FOXP4‐AS1.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations